Knowledge, Attitude, and Practices of Sugar-sweetened Beverages among Students in Malaysian University - Sohernea Kabilan; Shalini A/P Tiagarajan; Sumitha A/P T Nagarajah; Shweta AM Manisegaran; Navaneetha Cugati; Sivadas Ganapathy (Journal of South Asian Association of Pediatric Dentistry)
Sugar-sweetened beverages (SSBs) are beverages with added sugar that, in turn, add calories to an individual's normal diet and are the biggest contributors to added sugar intake. This excessive sugar consumption leads to obesity and other major health problems, including systemic diseases such as type 2 diabetes mellitus, cardiovascular diseases, liver diseases, and many more. Aims and objectives: The purpose of this study was to investigate students’ knowledge, attitude, and practices (KAP) concerning SSBs, as well as the factors that influence their KAP, at AIMST University. Data were acquired from 381 students via self-administered surveys that included sociodemographic and KAP information for the SSB questionnaire. Results: The results revealed that more than half of the participants are of normal weight, while fewer are overweight. Most of them associated sports drinks with the term SSB. The KAP score indicated good practice, a middling attitude, and weak knowledge. Participants who are overweight had much higher knowledge of SSBs, while people with normal weight had a higher attitude level toward SSBs (p < 0.05). Conclusion: The prevalence of SSB consumption among AIMST students from various faculties has shown good practice and somewhat of a good attitude toward SSB products. However, creative health promotion measures must be developed and implemented to minimize SSB consumption while also addressing emerging health challenges among the younger generation, such as obesity and diabetes. Oral health disorders, such as dental caries, can be minimized by reducing SSB consumption, particularly if ingested on a regular basis.